Controlled release of dinotefuran with temperature/pH-responsive chitosan-gelatin microspheres to reduce leaching risk during application. (1st February 2022) - Zhang, Qizhen; Du, Yu; Yu, Manli; Ren, Lirui; Guo, Yongfei; Li, Qinghua; Yin, Mingming; Li, Xiaolong; Chen, Fuliang
Abstract: Neonicotinoid-based pesticides are extensively used owing to their broad insecticidal spectrum and activity. We developed neonicotinoid dinotefuran (DIN)-loaded chitosan-gelatin microspheres using a spray-drying technology, resulting in a pH- and temperature-responsive controlled-release system. Upon introducing chitosan into the triple-helix structure of gelatin, the physically modified gelatin microspheres became smooth, round, and solid, improving their thermal storage stability. The spray-drying parameters were optimized using three-dimensional surface plots. When scaled up under optimal conditions, the corresponding loading content and encapsulation efficiency were 21.5% and 98.17%, respectively. Compared with commercial dinotefuran granules, our biodegradable composite carriers achieved the immobilization of dinotefuran to reduce pesticide leaching by 5.57–19.89% in soil, improved the soil half-life of DIN, and improved its cumulative absorption by plants. Therefore, the microspheres showed better efficacy against Trialeurodes vaporariorum . Our results confirm that this simple approach can improve the utilization efficiency of neonicotinoids, decrease leaching loss, and promote ecological safety. Graphical abstract: Unlabelled Image Highlights: The physically modified microspheres became round, solid, and stable. A pH- and temperature-sensitive, controlled-release microsphere system was developed. Dinotefuran-loaded gelatin-chitosan microspheres reduced the pesticide leaching. The soil half-life of dinotefuran was increased by 11 days with its accumulation in leaves. The microspheres showed a better efficacy against Trialeurodes vaporariorum .